2022
DOI: 10.1007/s10823-021-09439-7
|View full text |Cite
|
Sign up to set email alerts
|

“I Know Hyena. Do you Know Hyena?” Challenges in Interpreter-Mediated Dementia Assessment, Focusing on the Role of the Interpreter

Abstract: Dementia assessment requires functional communication and interaction between healthcare professionals and the patient being assessed. These can be affected by the requirement for an interpreter to communicate with the patient. The purpose of this study was to elucidate the interactions between patient, healthcare professionals and interpreter, focusing on the role of the interpreter and the challenges that may arise in interpreter-mediated dementia assessment. The study had an ethnographic design in which the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…To our knowledge, this is the first time that training designed to upskill interpreters in dementia and cognitive assessments will have undergone evaluation in a RCT. A number of studies have observed the influence that interpreters can have on the accuracy of cognitive assessments, and recommended training and resourcing to optimize interpreters’ performance, 13 , 15 , 22 yet the training has not undergone rigorous evaluation. To address this gap, we have partnered with key stakeholders in the interpreting and dementia care sectors to co‐design an online training resource for interpreters.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…To our knowledge, this is the first time that training designed to upskill interpreters in dementia and cognitive assessments will have undergone evaluation in a RCT. A number of studies have observed the influence that interpreters can have on the accuracy of cognitive assessments, and recommended training and resourcing to optimize interpreters’ performance, 13 , 15 , 22 yet the training has not undergone rigorous evaluation. To address this gap, we have partnered with key stakeholders in the interpreting and dementia care sectors to co‐design an online training resource for interpreters.…”
Section: Discussionmentioning
confidence: 99%
“…Generic interpreter training may not equip interpreters with the necessary skills to manage the complex demands of interpreting cognitive assessments, potentially leading to inaccurate assessments, miscommunication, and/or poor patient/client experience. 15 , 21 Most professional interpreters in Australia have received training and have passed an examination to gain certification from the National Accreditation Authority for Translators and Interpreters (NAATI). However, prior to 2007, training was not a prerequisite to examination, and some professional interpreters still lack training.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations